Unrewarding wealth : the commercialization and collapse of agriculture in a Spanish Basque town - Greenwood, Davydd J. (Cambridge [Eng.] : New York : Cambridge University Press, 1976)
This work contains a history of farming in a Spanish Basque town where the farmers changed their subsistence farms into highly profitable commercial enterprises in response to demand created by tourism and industrialisation. In the period of highest profits however, the young Basques began to abandon their farms and turned to factory work at a much lower standard of living. The institutional problems within both the farm families and the local municipality are described along with the Basque ideas about the dignity of work to help explain why such successful maximisers of economic gain should ultimately reject economic rewards in favour of other values. Davyyd Greenwood carefully examines the relationships between workers of economic gain and the institutional and cultural aspects of human behaviour. In particular he argues that human behaviour is a complex mix of motivations and that our methods must reflect this complexity. - See more at: https://www.betterworldbooks.com/unrewarding-wealth-id-0521210216.aspx#sthash.lsd6A2tT.dpuf
Includes bibliographical references: p. [217]-218 and index
lje 14/06/2017
Loans
Keywords: Agriculture--Economic aspects; Social conditions; Spain--Hondarribia